Stage discharge curve for Guillemard Bridge streamflow sation based on rating curve method using historical flood event data - Ros F.C.; Tosaka H.; Sidek L.M.; Desa M.N.; Arifin K. (Institute of Physics Publishing, 2023)
The purpose of the stage-discharge curves varies from water quality study, flood modelling study, can be used to project climate change scenarios and so on. As the bed of the river often changes due to the annual monsoon seasons that sometimes cause by massive floods, the capacity of the river will changed causing shifting controlled to happen. This study proposes to use the historical flood event data from 1960 to 2009 in calculating the stage-discharge curve of Guillemard Bridge located in Sg. Kelantan. Regression analysis was done to check the quality of the data and examine the correlation between the two variables, Q and H. The mean values of the two variables then were adopted to find the value of difference between zero gauge height and the level of zero flow, a, K and n to fit into rating curve equation and finally plotting the stage-discharge rating curve. Regression analysis of the historical flood data indicate that 91 percent of the original uncertainty has been explained by the analysis with the standard error of 0.085. Published under licence by IOP Publishing Ltd.